Superior wear resistance in a TaMoNb compositionally complex alloy film via in-situ formation of the amorphous-crystalline nanocomposite layer and gradient nanostructure. (15th January 2023) - Luo, Jiasi; Sun, Wanting; Liang, Dingshan; Chan, K.C.; Yang, Xu-Sheng; Ren, Fuzeng
Abstract: Metallic alloys with exceptional wear resistance have long been an attractive prospect for their enhanced safety, reliability, and service duration. Herein, we propose a strategy to achieve superior wear resistance via the in-situ formation of an amorphous-crystalline nanocomposite layer and gradient nanostructure during wear at elevated temperatures. This strategy was demonstrated in a compositionally complex alloy TaMoNb film with a columnar grain structure upon sliding wear at 300 °C. In contrast to the surface layer formed at room temperature (RT), which consists of irregularly shaped TaMoNb nanograins with non-uniform size and distribution in the amorphous oxide matrix, a dense 300 nm-thick nanocomposite layer comprising equiaxed nanograins of only ∼6 nm embedded in the amorphous oxide matrix is formed during wear at 300 °C, below which is a 600 nm-thick plastic-deformation region that exhibits gradient nanostructure. The microstructure induced by wear at 400 °C shows the presence of a 30 nm-thick amorphous layer below the nanocomposite surface layer but no appreciable plastic deformation in the base film. Consequently, the TaMoNb film exhibits a remarkably low wear rate upon wear at 300 °C that is less than 25% of those at RT and 400 °C. Such superior wear resistance is attributed to the specific wear-induced microstructure generated at 300 °C, which has high strength and large homogeneous deformation. Thus, this work offers a new strategy for designing self-adaptive wear-resistant alloys for application in extreme thermo-mechanical service environments. Graphical abstract: Image, graphical abstract